O princípio da homotipose em Karl Pearson: aspectos biológicos e estatísticos (1899 1906) - Venturineli, Katia Regina (2010)
Karl Pearson (1857-1937) is usually known for his contribution to mathematics and statistics. Besides, he presented (1901-1902) a proposal to Biology: The homotyposis principle. He applied the statistics to test it. Pearson´s proposal generated an argument with William Bateson (1861-1926) and other biologists. This dissertation´s aim is, firstly, to describe Pearson´s proposal in relation to homotyposis in accordance with both biology and statistics terms, and then, to analyse it. It should also check if the negative reception by the Mendelians and other biologists was due to a weak basis. This dissertation contains an introduction and four chapters. Chapter 1 discusses some Karl Pearson´s previous statistical studies. Chapter 2 is about his career and professional interests dealing with biological aspects in relation to homotyposis. Chapter 3 analyses Pearson´s statistical concepts and its correlation verified in his homotyposis studies. Chapter 4 presents some conclusions about what was discussed in the previous chapters. This study showed that Pearson applied adequate methods accurately regarding statistics, such as collection, counting, tabulation, calculation and comparison of data according to the data studied. Nevertheless, the conception of homotyposis, its starting point in biological terms, was mistaken